Knowledge, Attitude and Practice of Health Care Professionals Towards Universally Applied Behavior Modification Techniques for Management of Pediatric Patients - Wahid, Maham; Yousuf, Ajmal; Ali Shah, Pir Jaawad; Shah, Dr Jawad Ali; Bhangar, Faisal; Shah, Muzammil (Pakistan Armed Forces Medical Journal, 2022)
Objective: To evaluate health care professionals' knowledge, preference and experience about various universally applied behaviour modification techniques for managing anxiety in pediatric patients.Study Design: Cross-sectional survey.Place and Duration of study: Operative Department Armed Forces Institute of Dentistry Rawalpindi in Apr 2020.Methodology: An online questionnaire was circulated among 100 Health Care Professionals of Rawalpindi, including general practitioners, consultants and post-graduate residents of different fields of medicine and dentistry involved in the clinical care of pediatric patients, which included socio-demographic details, closed-ended questions about their knowledge about different universally applied behaviour modification techniques for management of anxiety, their preference in usage and factors affecting selection particular behaviour modification techniques for management of anxiety.Results: 66 (84.61%) of the healthcare professionals were aware of the different universally accepted behaviour modification techniques; 12 (15.38%) were unaware of such techniques. 33 (42%) of the practitioners admitted that pediatric patients showed non-compliance to simple non-invasive procedures while 45 (58%) to invasive procedures. 49 (62.3%) of respondents used universally accepted behaviour modification techniques. 74 (94.87%) of the respondents opted Tell-Show-Do, while the majority opted combination of different behaviour modification techniques as the preferred method of universally accepted non-pharmacological behavior modification technique.Conclusion: The majority of the health care professionals preferred Tell-Show-Do and positive reinforcement techniques along with the combination of various non-pharmacological techniques as the most commonly adopted techniques for management of anxiety in pediatric patients.